The macroeconomic approach to the interpretation of accounting information - Dossayeva, A. Z. (Journal of Economic Research & Business Administration, 2015)
In the scientific article is represented by the economic interpretation of the accounting system, which arranges for a single featured a large variety of accounts used in various companies and industries. We recommended macroeconomic approach to the modification of the accounting system to the national accounts could be produced by the aggregation of accounting data. Reasonable harmonization of the two accounting systems, the macroeconomic approach to the interpretation of accounting, it is possible in their interpretation and classification of certain items of income, expenses, assets, etc. Therefore, the information is subject to significant accounting treatment in order to comply with the concepts, definitions and classifications of the SNA. Thus, the mechanism of interaction between existing systems in parallel, would allow each to perform a useful function in a specific state-wide control system.